Health care providers' experience of research activities in public sector health facilities in the Western Cape Province of South Africa - Ndlovu, Linda (Department of Public Health and Family Medicine, 2021)
There is a significant amount of public health research conducted within provincial health facilities in South Africa, whose findings have a positive impact on the delivery of health services. This includes clinical, epidemiological, health systems and health services research, often initiated by post‐graduate students, independent academics researchers, as well as research institutions. Although researchers commonly commit to providing feedback to the provincial department and facilities, there is little evidence to confirm that research feedback is subsequently provided. Little contextualized empirical evidence is available to guide action, particularly for frontline health care providers, who often have the responsibility to host these research activities. The aim of this study was to explore the experiences of healthcare providers with research activities hosted in health facilitiesin the Western Cape province of South Africa. A mixed-method, cross-sectional study was conducted utilising an online survey (n= 19), and semi-structured interviews (n=3) with frontline health care providers (research gatekeepers). Descriptive analyses characterized respondents and their experience of research. Qualitative thematic analysis took on an inductive approach by identifying themes as they emerged from the data and cross comparing these with findings from the scoping literature review. Findings provided insight into how research conduct is experienced by those on the frontline in public health facilities on the provincial district platform. This is particular to the Western Cape province, which has a specific health department administration system. The following themes emerged: perception of research burden on services, understanding of the research approval process, autonomy to deny researchers access to the health facility due to overburden of research, the frequency or occurrence of research feedback after completion of a project, and interpersonal dynamics between researchers and gatekeepers as it relates to research conduct in facilities. This research reports on empirical evidence of perspectives from frontline health care providers on their experience with health research in a particular provincial context. The findings could form the basis of a study with a much larger sample size to inform how research feedback can be translated in a way that directly impacts on the uptake in the frontline.